The Music of Brazil - Appleby, David P. (University of Texas Press, 2021)
Here is the most comprehensive history of Brazilian music available in English. Concise yet remarkably detailed, it provides professional musicologists and music lovers alike with a clear outline of the major trends, important composers, and currents of thought that have shaped the folk, popular, and art music that are an important part of Brazil's unique cultural heritage. The Music of Brazil contains over seventy musical examples representing musical idiom and form throughout recent history. A useful glossary introduces the reader to the key terms of Brazilian music, from agogô-a percussion instrument composed of two bells-to xocalho-a wooden or metal rattler